Reliability assessment of pre -post test questionnaire on the impact of a daylong clinical pharmacology workshop among medical professionals - Biswas, Arunava; Sen, Sukanta; Ray, Krishnangshu (Asian Journal of Medical Sciences, 2019)
Background: Pretest-posttest questionnaire are often used during workshop to assess the impact of a program on the participants. However, the reliability of such data collection ‘tool’ is not often judged. There is lack of evidence supporting the authentication of such research instrument. Aims and Objective: This study was conducted to assess the reliability of prepost test questionnaire comprising MCQs, on participants attending a one-day workshop on clinical pharmacology at a teaching hospital in eastern India. Materials and Methods: Pre and post test questionnaire comprising 15 MCQs covering different aspects of ‘Good Clinical Practices’ on which several presentations were later delivered by experts were distributed to (n=42) participants in a one-day oriented workshop within stipulated time period and their feedback were collected and statistically analyzed after the workshop was over. Results: The average number of MCQs attempted in the pretest questionnaire was 12.42 and in posttest were 14.44 by the participants. The workshop participants increased their percentage of correct answer score from an average of 48.4 in pretest to a statistically significant 88.73 in posttest (p<0.0001). Conclusion: Pre/post questionnaire could be effective and reliable tools in meeting stipulated learning objectives and help in assessing the aftermath of an educational program.